Studi Sifat Mekanis Biokomposit Serat Ijuk dan Serat Sabut Kelapa Untuk Aplikasi Helm Kendaraan Roda Dua - Muradin, Muradin; Hasbi, Muhammad; Imran, Al Ichlas (Teknik Mesin Universitas Halu Oleo, 2019)
Motorcycles are a popular means of transportation in most countries in Asia and developing countries including Indonesia. In the event that riding a motorcycle, the user must use a helmet to keep his head from collisions when accidents occur. The research aims to utilize palm fiber and fiber biocomposites as raw material for two-wheeled vehicle helmets. The composition of the fiber volume fraction is 40:60%, 50:50%, 60:40%, polyester resin matrix, and catalyst. The mixture is printed in the form of a biographic panel and formed an impact test specimen and hardness test. The results obtained that the highest impact strength value of 0.013 J/mm2 and the highest hardness value of 21.367 kg/mm2 in the fiber composition of 60:40%. The value of the lowest impact strength is 0.005 J/mm2, and the lowest hardness value is 16.523 kg/mm2 on the fiber composition 40:60%. Keywords: biocomposite, palm fiber, coir, polyester, hardness, and impact